Diagnosis Approach For Head of Pancreatic Carcinoma with Hepatitis B - Ida Bagus Putra Narendra; I Made Suma Wirawan Wangaya (Jurnal Inovasi Global, 2025)
Pancreatic cancer is one of the deadliest malignant tumor with short overall survival, 3-5 months survival and 5 years 3% at an advanced stage. Pancreatic cancer is the fourth leading cause of cancer death globally according to Global Cancer Statistics 2024. Symptoms of pancreatic cancer are nonspecific in the early stages causing patients to come on at an advanced stage, which contributes to poor outcomes, decreased quality of life and shortened overall survival. A 35-year-old man came in with the main symptoms of abdominal swelling and jaundice from a month earlier. Symptoms are accompanied by sensations of a full abdomen, nausea and edema of both lower extremities. Eye examination shows pale conjunctiva and scleral jaundice, warm extremities and there is pitting edema in the pre-tibia region. Laboratory results showed anemia accompanied by an increase in direct bilirubin. The HbsAg test showed positive. Ultrasound examination showed the impression of obstructive jaundice with a suspected mass in the head of the pancreas. There is intrahepatic bile duct dilation (IHBD) (Figure 1) and extrahepatic bile duct (EHBD) features with mud and ascites features and abdominal CT scan shows masses in the head of the pancreas. Pancreatic carcinoma mostly occurs at the age of 60-80 years, 85% of patients have clinical symptoms of obstructive jaundice, pruritus, dark urine, and obstructive bile ducts. Symptoms of malignancy are associated with a gradual onset, weight loss, and are sometimes accompanied by abdominal pain. Bile obstruction can be caused by tumor, especially in the caput of the pancreas i.e. a slight increase in bilirubin levels, which spontaneously fall off without any intervention. In pancreatic cancer, bilirubin levels tend to rise when there is no intervention. Pancreatic caput cancer is relatively rare but has a high malignancy. It is possible that the inactive HBV-pancreatic cells then encode some functional proteins that induce local inflammation. HBV can trigger the proliferation and migration of pancreatic cancer cells. Making a diagnosis is often difficult because symptoms usually appear after the cancer has reached an advanced stage.